The effects of supplementary feeding of traditionally managed Bunaji cows - Otchere, E.O. (1986)
The production performance of Bunaji cows on supplementary feeding was investigated. Supplements of cottonseed cake, molasses-urea or fodder bank were fed to Bunaji cows to evaluate effects on birth and 1-year weight of calves and their viability to 1-year, and milk yield of cows under an agropastoral management system. Data on performance parametres included.